Sport Students' Hematology Profiles as Detected By The Automatic Sysmex XP-300 at Keberkatan Olahraga Senior High School In Aceh - Munadi Munadi; Desiana Desiana; Cut Murzalina (Journal of Social Research, 2025)
Physical activity has long been linked to modifications in hematologic profiles as the body's compensating response to the stress of physical training. Several earlier research studies have discovered that physical activity impacts red blood cells, leukocytes, and platelets, while the findings remain contentious. Monitoring an athlete's hematologic profile is critical for effective training management. The purpose of this study is to analyze the hematologic profile of young adults who attend sports-specialized schools. This cross-sectional study included 30 students (15 males and 15 females). Blood samples were collected using standard venipuncture methods and examined on an automatic Sysmex XP-300 analyzer. The analytical results revealed that all participants had mean or median values for each complete blood count (CBC) parameter and leukocyte differential count that were normal for the general population. Females showed greater mean/median values for all CBC indices except hemoglobin, hematocrit, erythrocytes, MCHC, and RDW. For ESR (erythrocyte sedimentation rate), all participants exhibited normal levels, with females having greater levels. The leukocyte differential count showed that the results for male and female patients were comparable. Sport students' hematologic profiles are normal for the overall community. However, it is critical to remember that physical activity alters the blood and its components, prompting the need for hematologic indices specific to athletes or sports students.